Draft Genome Sequence of the Host-Restricted Salmonella enterica Serovar Abortusovis Strain SS44 - Deligios, M. (American Society for Microbiology, 2014)
Salmonella enterica serovar Abortusovis is a pathogen strictly adapted to ovines, in which it causes abortion. To enhance our understanding of this pathogen, we assembled the first draft sequence of an S. Abortusovis genome (strain SS44). The obtained genomic data might facilitate the study of S. enterica evolution and host adaptation.